Peningkatan Minat Dan Keberanian Siswa Melakukan Tanggapan Dalam Pembelajaran Berbicara Melalui Model Readers Respons Siswa Kelas VII SMP Negeri 17 Makassar - Desy Ayu Andhira (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
This research aims to describe the planning, implementation and assessment of increasing students' interest and courage in responding in speaking learning through the Response Readers model for class VII.1 students at SMP Negeri 17 Makassar. This research approach uses a classroom action research (PTK) approach. This type of research is descriptive qualitative. The data collection technique used in this research was a test technique and observation with two cycles. The data analysis techniques used are quantitative and qualitative analysis techniques. The results of the research show that the implementation of increasing students' interest and courage in responding in learning to speak through the Readers Response model for students in class VII.1 of SMP Negeri 17 Makassar showed significant results which were marked by an increase in the number of students who had very good and good grades. decrease at the level of sufficient and poor student categories.